Adaptive bandwidth allocation for per-station fairness on wireless access router - Vasaka Visoottiviseth (2018)
According to the nature of IEEE 802.11 wireless LAN, the bandwidth is shared among wireless devices. However, the bandwidth could not be fairly shared among stations, because some users may use greedy applications which prevent other applications from connecting to the Internet. These applications are for example, video streaming applications, download accelerators and P2P applications. Moreover, Distributed Coordination Function (DCF) mechanism provided in the 802.11 MAC protocol originates the per-flow unfairness problem between uplink and downlink flows, as uplink flows usually dominate downlink flows and leads to unfair bandwidth allocation among wireless stations. In this paper, we propose an adaptive bandwidth allocation mechanism to provide per-station fairness. The proposed scheme can control the wireless traffic for fairness bandwidth allocation among stations. The bandwidth of each station can be adjusted to minimize the remaining bandwidth. The proposed scheme also covers a method to prevent domination of uplink flow which affects per-station fairness. Furthermore, the proposed scheme can be implemented on wireless access router. Hence, in order to support legacy wireless clients, our solution can be efficiently used. ©2010 IEEE.